PLATELET ANTIAGGREGANTS: MECHANISMS OF ACTION AND USE ASOCIED RISKS - PALOMO G, Iván F.; TORRES U., Constanza I.; MOORE-Carrasco., Rodrigo E.; ALARCÓN L., Marcelo A.; MARAGAÑO L., Patricio J. (Vitae, 2009)
Cardiovascular diseases are the main cause of death in the world. Next to efforts to reduce the cardiovascular risk factors, several drugs are resorted to decrease morbimortality associated to these diseases: antihypertensive, antidiabetic, hypolipemiant and platelet antiaggregant drugs are used among others. Due to the participation of platelets, not only in the early stages of the atherogenesis but also in the artery thromboses, the use of platelet antiaggregant drugs is very relevant in the primary and secondary prevention of the artery thrombosis. In this review, after a brief description of the primary hemostasis, aspects of antiplatelet like mechanisms of action and use asocied risks during the last 10 years are adressed. Primarily literature source was www.pubmed.com. The terms used in the search were: platelet antiaggregant, aspirin, dipyridamole, clopidogrel, abciximab, among others, then we searched the full texts of articles of interest and also used some hematology books.